Multiplicative decomposition and infinite divisibility of the mandel distribution - Virchenko, Yu.P.; Vitokhina, N.N. (Інститут математики НАН України, 2005)
Inﬁnite divisibility of the Mandel distribution that arises in quantum optics is proved. On the basis of this fact, the multiplicative decomposition of this distribution into the countable convolution of some Poisson distributions is constructed.